2019
DOI: 10.1080/08820538.2019.1684525
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Manifestations of Inflammatory Bowel Disease

Abstract: Purpose: To evaluate detailed corneal parameters of inflammatory bowel disease (IBD) patients, including Crohn's disease (CD) and ulcerative colitis (UC) patients, and to assess associations between anterior segment values and other clinical variables. Methods: This prospective cross-sectional case-control study at a tertiary referral center included 30 CD patients, 36 UC patients and 80 age-and gender-matched controls with no ocular symptoms or ocular surface disorders. All study participants underwent a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(33 reference statements)
1
14
0
6
Order By: Relevance
“…Moreover, a significant correlation resulted between inflammatory markers, OSDI, and the Schirmer test. These findings are consistent with the idea of multiorgan inflammatory involvement in PsA disease sine-PsO [8,31] as demonstrated in other chronic inflammatory disorders, such as PsO [8][9][10][11][12][13], diabetes mellitus [32,33], and thyreopathies [34]. In this context, the presence of dry eye might reflect the inflammatory status being an indicator of the systemic involvement in PsA [35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, a significant correlation resulted between inflammatory markers, OSDI, and the Schirmer test. These findings are consistent with the idea of multiorgan inflammatory involvement in PsA disease sine-PsO [8,31] as demonstrated in other chronic inflammatory disorders, such as PsO [8][9][10][11][12][13], diabetes mellitus [32,33], and thyreopathies [34]. In this context, the presence of dry eye might reflect the inflammatory status being an indicator of the systemic involvement in PsA [35].…”
Section: Discussionsupporting
confidence: 88%
“…As widely documented from both case-series studies and population-based studies, the presence of PsO is related to dry eye disease and its possible complications (as keratopathy) [10,11]. Dry-eye disease, in systemic inflammatory diseases, is associated with elevated levels of pro-inflammatory cytokines in tear film [12,13] Data concerning dry eye syndrome in PsA patients without PsO is lacking to date.…”
Section: Introductionmentioning
confidence: 99%
“…DED is the most common eye pathology because this disease can emerge as a primary phenotype; that is, a local immune response is generated and sustained in the ocular surface and draining lymph nodes [9]. DED is also found as a secondary phenotype, where both autoinflammatory (e.g., colitis) [10,11] and autoimmune diseases (Sjögren's syndrome, rheumatoid arthritis, and lupus) present DED symptoms [12][13][14]. The relevant finding that DED onset precedes autoimmune and non-autoimmune diseases in several patients is puzzling, and it has attracted interest from researchers worldwide, but the pathways remain to be elucidated.…”
Section: Dry Eye Diseasementioning
confidence: 99%
“…For example, there has been limited research into how the cornea is affected in IBD patients. Recent research, however, found Crohn’s disease patients who showed no symptoms of ocular involvement were observed to have reduced corneal thickness and reduced tear quantity ( 30 ).…”
Section: Autoimmune Disorders and Their Ocular Effectsmentioning
confidence: 99%